Penerapan Prinsip Keadilan dalam Pembagian Risiko Kontrak Proyek Oil And Gas - Ramdhan, Muhammad; Samian, Samian (Syntax Corporation, 2026)
Oil and gas projects are characterized by high technical complexity, large capital investment, and significant risk exposure, including technical, cost and time, health and safety (HSE), environmental, commercial, and regulatory risks. Contract design in oil and gas projects—particularly EPC/EPCI contracts and Production Sharing Contracts (PSC)—often raises issues of fairness in risk allocation between project owners and contractors. Imbalanced risk allocation practices tend to increase bid prices, trigger claims, and lead to contractual disputes. This article analyzes the application of fairness principles in risk allocation for oil and gas project contracts using a qualitative–normative approach through literature review and doctrinal analysis. The study integrates project risk allocation concepts, theories of fairness in contract law, and international standard practices such as FIDIC 2017 and knock-for-knock clauses. The findings indicate that fairness in risk allocation can be operationalized through criteria of control, capability, risk–reward symmetry, procedural transparency, and systemic impact. This article proposes a Fairness-Oriented Risk Allocation Framework (FORAF) as a conceptual approach to evaluate and design fairer risk allocation in oil and gas contracts. The framework is expected to reduce dispute potential and enhance the sustainability and performance of oil and gas projects, particularly in developing countries such as Indonesia.